An Assessment of select market timing strategies’ performance in Nairobi Securities Exchange - Ng’ang’a, Judah (Strathmore University, 2019)
Herding behavior among Kenyan traders in the capital markets has been majorly attributed to low levels of income and lack of knowledge in trading principles. This focus of this study was on the latter challenge. The study is meant to benefit market traders in determining optimal entry and exit points in equity markets. The study evaluated the performance of three market timing strategies namely the relative strength index (RSI), simple moving averages (SMA) and hidden Markov model (HMM). The data considered in this study included the share price of the NSE-20 index over the period 2004-2018 triangulated to the perceptions and opinions of trading experts in Kenyan fund manager firms. The performance of market-timing strategies in this study was determined by a strategy’s average annual returns, Sharpe ratio as well as a market timing ability. Using Henrikson and Merton market timing model, this study shows that all the market timing strategies have positive market timing strategies, with HMM having the best market timing ability. By accommodating the autoregressive nature of financial prices this study examined the ability of the strategies to time the market using an autoregressive distributed lag (ARDL) model. The model shows that all the strategies lack the ability to time the market but just like in Henrikson and Merton model, HMM performances ranks best among the three strategies. Over the period 2004-2018 the Sharpe ratio of all the market timing strategies exceed that of SBH. The same is observed when simulated data is used instead of the observed data, on individual stocks as well as in a portfolio setting. When all the tests are considered the performance of HMM strategy ranks first followed by SMA, RSI while SBH was determined to be the least profitable trading strategy. In Kenya, this study found that investors are averse to market timing strategies and tend to herd towards buy and hold strategy. Given the low profitability of the SBH strategy in NSE, this study recommends the use of HMM as trading strategy to determine entry and exit points.
A thesis submitted in partial fulfillment of the requirement for the Degree of Master of Commerce at Strathmore University